Estimating cover preferences of seladang (Bos gaurus hubbacki) in Krau Wildlife Reserve, Pahang. - Yusof, Ebil (Forestry Department Peninsular Malaysia, 2009)
Home range of seladang consisting of mainly primary forest, secondary forest and agricultural area. Their movement the home range depending on the availability of horizontal cover. Amount of cover for seladang within their home range was one the requirements for the stability of seladang population. Changes in land use and land use activities along the boundary of the Krau Wildlife Reserve (KWR) caused a cumulative effect of disturbance to the wildlife species, especially for herbivorous. Determination of horizontal cover as a result of human actions onto seladang (Bos gaurus hubbacki) and their habitat will help the management agency to outline the monitoring protocol for the species especially when they consider reintroducing the species into the wild. The Krau Wildlife Reserve comprised eleven seladang management units (SMUs) of approximately 638 km2. However, this study focused only SMU 1 to SMU 7, SMU 1, SMU 2, SMU 3 and SMU 5 were block of primary forest with a total area of 6313.5 ha. While. SMU 4. SMU 6 and SMU 7 were recognised as disturbed condition as a result of forest-encroachment practices with a total area of 5820.1 ha. The results indicated that SMU 1, SMU 2, SMU 3 and SMU 4 had less than 70% of horizontal cover requirement. Horizontal cover for SMU 5, SMLI 6 and SMU 7 ranged between 71.75% and 74.79%. Only SMU 2 was low in term of cover at 50.73%.